Landslip Warning System in Hong Kong - Over 40 Years of Evolution - Chung, Philip W.; So, Sunny Tc; Chu, Edward Kh (Current Chinese Science, 2023)
Background: Hong Kong is situated on the coast of the south-eastern tip of China. A sub-tropical climate brings this coastal city a rainy season from April to October each year. Rainfall intensities as high as 50 mm to 100 mm per hour and 250 mm to 350 mm in 24 hours are not uncommon. With the hilly terrain and densely populated development, Hong Kong is susceptible to land-sliding during heavy rainstorms. Concerted efforts have been made by the Geotechnical Engineering Office (GEO) of the Hong Kong Special Administrative Region Government, to operate and enhance a territory-wide Landslip Warning System continuously, as a major component of landslide risk management tools in Hong Kong, since its establishment in 1977. Forewarning the public of possible landslide risks due to heavy rainstorms and triggering an emergency system within the government to deal with landslide incidents are the major objectives of the Landslip Warning System. This paper presents the development and enhancement of the comprehensive people-centred early warning system for landslides in Hong Kong, based on a framework of an early warning system with four major elements, including risk knowledge, monitoring and warning services, communication and dissemination, and response capability. Methods: With good quality landslide, rainfall and slope databases, landslide prediction models have been developed and continuously updated using statistical means to assess the severity of landslides based on real-time rainfall and rainfall forecast. For the purpose of an effective and robust operation of the Landslip Warning System, the latest Internet of Things (IoT) and cloud computing technologies have been deployed to operate the GEO Rainguage System collecting, transmitting and processing real-time rainfall data over the territory of Hong Kong, and to enhance system redundancy and resilience for data analysis and information dissemination. Results: To have an effective communication and dissemination of the Landslip Warning information to the community, various public education activities have been carried out regularly to promote public awareness of landslide risks and promote personal precautionary measures during heavy rainstorms. Conclusion: Well-established procedures for the operation of the Landslip Warning System have been developed to trigger the internal emergency mechanism within the government to deal with the landslide danger, with the support of innovative solutions to enhance the capability and efficiency of emergency responses.
Keywords: landslide prediction